Managing the quality of sleep among elderly patients using the Pittsburgh Sleep Quality Index. Issue 1 (1st June 2011) - Cheah, E; Rajaram, S; Cheah, E; Sidek, N; Tan, M H; Fadillah, F; Zheng, D; Hamid, H
Abstract : Introduction: Sleep is a necessary part of life. Assessment of sleep patterns enables the nurse to intervene immediately by implementing interventions with the client, or by referring the client for further assessment. Method: The Pittsburgh Sleep Quality Index (PSQI) is an effective instrument created by Buysse et al in 1989. It differentiates 'poor' from 'good' sleep by measuring seven areas: subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency and sleep disturbances, use of sleep medication and daytime dysfunction over the last month. The client self relates each of these seven areas of sleep. Scoring of the answers is based on a 0 to 3 scale, three reflects the negative extreme on the Likert scale. A sum of '5'or greater indicates a 'poor' sleeper. Result: Seven patients who had sleeping problems were assessed. Data using the PSQI was collected from the 18th of June till the 18th of July 2010. Out of these seven patients, four of them were found to a sum of 5 to 6 as their global PSQI score. Two of them were given sleep medication to improve their sleeping patterns and the other two of them were referred to a psychologist. Three of the patients were found to have subjective sleep problems; two of them were overweight and were asked to start an exercise program. The other patient was found to lead a sedentary lifestyle and was encouraged to be more active. Conclusion: The PSQI can be used for both initial assessment and ongoing comparative measurements with older adults across all health settings.